Analisis Kesalahan Siswa dalam Menyelesaikan LKPD berbasis Inkuiri Terbimbing Materi Trigonometri Kelas X - Sulia Anis Prastika; Abi Suwito; Susanto, Susanto (Griya Journal of Mathematics Education and Application, 2023)
This research aims to analyze students' errors using the Newman procedure in working on LKPD-based Guided Inquiry in class X Trigonometry material. This type of research is descriptive qualitative research. The subjects of this research were class X high school students. The data collection technique used was through the results of work on LKPD based on guided inquiry on Trigonometry material, observations, and interviews with class X students. Based on the analysis that has been carried out, it can be concluded that the errors experienced by high school students when working on LKPD-based guided inquiry on trigonometry material using the Newman procedure are errors in reading the problem (reading), understanding the problem (comprehension), transformation of the problem (transformation), process skills (process skills) and coding/drawing conclusions (encoding). From the results of the analysis above, it can be used as material for developing problems or difficulties faced by students in learning mathematics, especially in Trigonometry material in the future. Apart from that, there is a need for learning strategies that can embed concepts and understanding of previously studied material.